Rare intestinal fistula caused by primary lymphoma of the gastrointestinal tract: Two case reports and literature review. Issue 27 (July 2018) - Zhuang, Nan; Zhu, Qingli; Li, Wenbo; Wang, Miaoqian; Yang, Qian; Liu, Wei; Li, Ji; Yang, Hong; Zhou, Weixun
Abstract: Rationale: Primary lymphoma that arises from the intestine is an uncommon malignant tumour, while intestinal fistula caused by primary lymphoma is even rarer. Non-specific clinical performance makes early diagnosis difficult, although imaging modalities might play an essential role in the detection of intestinal fistula. Patient concerns: Patient 1: A 60-year-old male hospitalized with diarrhoea and abdominal pain for seven months underwent computed tomography enterography (CTE) that demonstrated ileum internal fistula and ileac-sigmoid colon fistula. Ultrasound (US) showed small intestinal wall thickened and development of a fistula of the sigmoid colon due to malignance. Patient 2: A 43-year-old male presented with abdominal pain and diarrhoea lasting one year. US revealed a fistula between the sigmoid colon and the ileum, and CTE showed that the wall of the partial sigmoid colon was abnormally thickened and enhanced with an ileal-sigmoid fistula that strongly suggested the diagnosis of lymphoma. Diagnoses: Both the two patients were diagnosed as intestinal fistula caused by primary non-Hodgkin's intestinal lymphoma. Interventions: The patient 1 underwent surgery followed by chemotherapy. The patient 2 accepted chemotherapy. Outcomes: Two patients' general conditions remained stable and the imaging revealed no recurrence after follow-up of about 12 months. Lessions: Cross-sectional imaging, such as US and CT, plays an essential role in intestinal lymphoma fistula diagnosis.